2011
DOI: 10.1016/j.jvs.2010.10.130
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year experience of femoral artery aneurysms

Abstract: FAAs have been uncommon and rarely isolated lesions. Surgical repair offered good results either in elective or urgent settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 15 publications
(34 reference statements)
1
39
0
1
Order By: Relevance
“…Isolated aneurysm of the SFA is a rare condition. In the thigh, the distribution of aneurysms is calculated as follows: 80% common femoral, 15% superficial femoral, and 5% profunda femoris artery [2]. Aetiologic factors include atherosclerosis, infections, arteritis, connective tissue disorders, human immunodeficiency virus, and trauma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Isolated aneurysm of the SFA is a rare condition. In the thigh, the distribution of aneurysms is calculated as follows: 80% common femoral, 15% superficial femoral, and 5% profunda femoris artery [2]. Aetiologic factors include atherosclerosis, infections, arteritis, connective tissue disorders, human immunodeficiency virus, and trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Aetiologic factors include atherosclerosis, infections, arteritis, connective tissue disorders, human immunodeficiency virus, and trauma. Some authors demonstrated a correlation with abdominal aortic aneurysms in 60% of the cases; 36% were bilateral [2]. The median age of presentation of SFA aneurysms is 75.7 years; men are most often affected (87%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…True atherosclerotic aneurysms of superficial femoral artery (SFA) are rare and often associated with other peripheral or aortic aneurysms [2], [3], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this region, aneurysms most frequently involve the common femoral artery (CFA), whereas true aneurysms of the superficial femoral artery (SFA) represent only 15% to 25% of femoral arterial aneurysms [1], [2], [3], [4], [5].…”
mentioning
confidence: 99%